Systemic and local inflammation in colorectal cancer - Rumba, Roberts; Cipkina, Sandra; Cukure, Fanija; Vanags, Andrejs (Acta medica Lituanica, 2019)
Background. Colorectal cancer (CRC) is the third most common cancer in the world. The cornerstone of CRC treatment is surgical resection. However, patients in the same TNM stage show different recurrence rates and survival. Of patients with a local disease without lymph node or a distant metastasis, 20–25% still develop recurrence. There is evidence that inflammatory reaction is one of the key elements in tumour development. Materials and methods. We reviewed literature on colorectal cancer and its relationships with the immune system, with special focus on local and systemic inflammatory reaction. The Pubmed and ClinicalKey databases were searched using the key words colorectal cancer, local inflammation, systemic inflammation, markers of inflammation. The relevant literature was reviewed and included in the article. Results. The immune system has two-sided relationships with cancer, so it not only performs anti-tumour activities, but can also promote tumour growth and spread. Research has shown that signs of local inflammation are associated with a better prognosis in CRC. Systemic inflammation has been associated with more aggressive behaviour and a worse prognosis for patients with several cancers, including CRC. Conclusions. Recent findings in tumour biology have improved our understanding of colorectal cancer and of the natural course of this disease. Several markers of local and systemic inflammatory reaction have been identified. The next step is to find the most accurate and applicable marker, so that this promising tool can be used in clinical practice and aid in decision making.